2019
DOI: 10.3390/ma12152467
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in the Microstructures of Annealed Cu–Zr Bulk Alloy and Cu–Zr Alloy Films

Abstract: Copper–zirconium bulk alloy and Cu–Zr alloy films are prepared by vacuum smelting and magnetron sputtering, respectively, and subsequently annealing is conducted. Results show that Cu–Zr bulk alloy and alloy films exhibit significantly different microstructure evolution behaviors after annealing due to different microstructures and residual stress states. CuxZr alloy compounds disperse at the grain boundary of Cu grains in as-cast and annealed Cu–Zr bulk alloys. However, unlike bulk alloys, a large number of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Magnetron sputtering has become an important method for preparing thin films due to its fast speed and good uniformity [12]. The alloy films with low solid solubility prepared by magnetron sputtering, such as Cu-Mn [13], Ag-Ta [14], Cu-Zr [15] and Cu-Ag-Cr [16], are usually in a metastable state, and their atomic diffusion and stress evolution behavior are easily affected by external fields [17]. In particular, as the thickness of the film decreases to the nanometer scale, the atomic diffusion and migration behaviors of the alloy films under the thermal, electric and stress fields become increasingly prominent [18].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetron sputtering has become an important method for preparing thin films due to its fast speed and good uniformity [12]. The alloy films with low solid solubility prepared by magnetron sputtering, such as Cu-Mn [13], Ag-Ta [14], Cu-Zr [15] and Cu-Ag-Cr [16], are usually in a metastable state, and their atomic diffusion and stress evolution behavior are easily affected by external fields [17]. In particular, as the thickness of the film decreases to the nanometer scale, the atomic diffusion and migration behaviors of the alloy films under the thermal, electric and stress fields become increasingly prominent [18].…”
Section: Introductionmentioning
confidence: 99%
“…The Mo-48.2% Ag films were prepared on PI substrates at room temperature, as shown in Figure 3 I. According to previous studies [ 33 , 34 ], the internal stress of the film can be released by forming particles on the film. Therefore, numerous “worm-like” particles were formed on the as-deposited Mo-48.2% Ag films.…”
Section: Resultsmentioning
confidence: 99%
“…Wo et al [7] have investigated how the precipitation of Cr can strengthen nanocomposite Cr/Cu–Cr multilayer films. Prior work demonstrated that the bulk material and the corresponding thin film material with the same composition might exhibit different microstructure evolution behavior after annealing [8]. The electrical conductivity and tensile strength of a Cu–Cr alloy can be significantly improved after annealing treatment [3].…”
Section: Introductionmentioning
confidence: 99%